All about flooble | fun stuff | Get a free chatterbox | Free JavaScript | Avatars    
perplexus dot info

Home > Numbers
Sum of Squares (Posted on 2008-09-26) Difficulty: 3 of 5
The sum of n+1 consecutive squares, beginning with the square of
n(2n+1), is equal to the sum of the squares of the next n consecutive integers.

   n=1      32 + 42 = 52
   n=2      102 + 112 + 122 = 132 + 142
      .
      .
      .
Prove that the proposition holds for all integers greater than zero.

See The Solution Submitted by Bractals    
No Rating

Comments: ( Back to comment list | You must be logged in to post comments.)
more generalized solution Comment 6 of 6 |

to more generalize this solution let f(n) and g(n) be two functions such that they have positive integer values for all integers n>0

then lets say we want to find what relationships f and g must have such that the sum of the first g(n)+1 squares starting at f(n) is equal to the sum of the next g(n) squares

in other words,

sum( [f(n)+t]^2 t=0 to g(n)) = sum( [f(n)+g(n)+t]^2, t=1 to g(n))

sum(f(n)^2+2f(n)t+t^2,t=0 to g(n))=sum([f(n)+g(n)]^2+2(f(n)+g(n))t+t^2,t=1 to g(n))

t^2 drops out of each side

f(n)^2(g(n)+1)+f(n)g(n)(g(n)+1)=(f(n)+g(n))^2g(n)+(f(n)+g(n))g(n)(g(n)+1)

f(n)(g(n)+1)(f(n)+g(n))=(f(n)+g(n))g(n)(f(n)+2g(n)+1)

now if f(n)=-g(n) both sides are zero, so we get f(n)=-g(n)

cancel out the f(n)+g(n)

f(n)g(n)+f(n)=f(n)g(n)+2g(n)^2+g(n)

f(n)=2g(n)^2+g(n)

f(n)=g(n)(2g(n)+1)

now if we set g(n)=n then we get f(n)=n(2n+1) and that is simply the problem given


  Posted by Daniel on 2008-09-27 11:55:04
Please log in:
Login:
Password:
Remember me:
Sign up! | Forgot password


Search:
Search body:
Forums (1)
Newest Problems
Random Problem
FAQ | About This Site
Site Statistics
New Comments (17)
Unsolved Problems
Top Rated Problems
This month's top
Most Commented On

Chatterbox:
Copyright © 2002 - 2024 by Animus Pactum Consulting. All rights reserved. Privacy Information